Trabalho decente e desenvolvimento: o salário como elo entre crescimento econômico e efetivação dos direitos fundamentais laborais - Menezes, Larissa Teixeira de (2014)
The present dissertative study focuses on salary analysis as a link between economic growth and development of both workers and State, also relating salary with the effectiveness of labor fundamental rights and decent work. This research aims to answer the following question: could decent work, especially salary, as a poverty reducer and source of development, represent an obstacle to economic growth and effectiveness of labor fundamental rights? The subject was approached with dialectical and deductive methods, using a qualitative theoretical-instrumental legal research. As procedure was used historical, comparative and interpretative methods, and also indirect documentation as research technique. From human rights and labor fundamentals analysis, the present work will analyze the centrality of salary in economic and social rights listing antagonistic features which constitute the core of salary in a hybrid way with economic and social dimensions. Neoliberal primers aim high productivity over salary and dignity of workers. In this context is highlighted the importance of a decent work agenda, exponent of International Labour Organization which worries about checking effectiveness to human rights internationally and to labor fundamental rights inside each country. Likewise, this work brings researches from International Labour Organization, DepartamentoIntersindical de Estatística, EstudosSocioeconômicos, InstitutoBrasileiro de Geografia e Estatística and other institutes, ratifying the relevance of imbricated study between salary, decent work and development combining with statistical data about the subject evolution and effectiveness of labor fundamental rights.